Restorative Justice for Victims of Cyber Sexual Harassment: Realizing Justice for Victims - Zulkarnein Koto; Sutrisno Sutrisno; Vita Mayastinasari; Ismail Koto (Faculty of Law, Universitas Pekalongan, 2022)
Sexual violence on social media is one of the negative impacts of technological developments. Sexual violence on social media can have both physical and psychological impacts on victims. This study focuses on an analysis of the urgency and orientation of implementing restorative justice in cyber sexual harassment crimes. This research is a normative legal research with a conceptual and statutory approach. The results of the study confirm that the urgency of RJ's approach in cyber sexual harassment crimes is because the characteristics of cyber sexual harassment crimes are the existence of victims' losses both physically and psychologically so that RJ-based law enforcement efforts are needed which emphasize victim recovery as well as perpetrator awareness. The orientation of realizing justice for victims through RJ has actually been facilitated in the TPKS Law. This emphasized that victims have the right to medical, social and mental rehabilitation, social empowerment, compensation, and social reintegration. The guarantee for the fulfillment of victims' rights further emphasizes that the main orientation of the TPKS Law is efforts to recover victims. In addition, the TPKS Law has also formulated an RJ orientation for perpetrators that prioritizes social and medical rehabilitation for perpetrators.